Ageism Kills Brands. Issue 4 (November 2022) - Anesbury, Zachary William; Bellman, Steven; Driesener, Carl; Page, Bill; Sharp, Byron
Market share growth requires building mental and physical availability among all category buyers. However, if younger category buyers are more likely to purchase new-to-market products, then perhaps younger buyers are, relatively speaking, more important for growth. This research investigates the relationship between category buyer age, brand buyer age, and brand failure. When sub-brand buyer age is younger than category buyer age, the sub-brand is likely to be (a) new-to-market or (b) growing in market share. Older-than-category sub-brand-buyer age is likely for sub-brands that are (a) declining or (b) dead. Results from 17 years (1998–2014) of U.K. household panel data, including 5, 913 sub-brands from 101 categories, show that age skews were uncommon (only 18% of sub-brands), and second, that growing, stable and declining sub-brands appealed equally to all ages. Finally, we identified that new launches and dead brands tend to skew to younger consumers, suggesting that new launches need to appeal to all ages to avoid failure.